PRODUÇÃO DE TILÁPIA-DO-NILO (Oreochromis niloticus) E DE ALFACE (Lactuca sativa) COM A INTEGRAÇÃO DE SISTEMA AQUAPÔNICO DE JANGADA COM A TECNOLOGIA DE BIOFLOCOS - LORENA CANGUSSÚ DE MÉLO (2025)
Within the contemporary field of aquaculture, aquaponic systems and biofloc technology constitute promising alternatives for advancing sustainability in the food industry, as both approaches minimize water loss and facilitate nutrient recycling. However, the studies on the integration of these systems are scarce; therefore, this line of research becomes necessary. In light of these considerations, the objective of the present study was to assess Nile tilapia (Oreochromis niloticus) production within floating raft aquaponic systems incorporating biofloc technology, by evaluating the growth performance of both the fish and leaf lettuce (Lactuca sativa) over a 42-day experimental period. A completely randomized experimental design was employed, consisting of two treatments: a floating-raft aquaponic recirculating system (AQ) and a floating-raft aquaponic system incorporating biofloc technology (AQBFT). Twenty-eight male Nile tilapia with a mean initial weight of 0.330 kg, as well as thirty-two leaf lettuce seedlings, were allocated to each module. The productive performance of Nile tilapia and leaf lettuce was evaluated in both systems. In the AQ system, the following results were observed: final weight (0.528 kg), daily weight gain (4.73 g/day), final biomass (14.80 kg/m³), and biomass gain (5.56 kg), all of which were significantly higher (P < 0.05) than those observed in the AQBFT system (0.474 kg; 3.37 g/day; 13.2 kg/m³; and 3.87 kg, respectively). Regarding lettuce growth performance, superior outcomes were likewise obtained in the AQ system, which exhibited significantly higher (P < 0.05) leaf weight (186.84 g), root weight (25.13 g), and total lettuce biomass (3.13 kg/m²) compared to the AQBFT system (76.56 g; 10.87 g; and 1.22 kg/m², respectively). The floating-raft aquaponic system incorporating biofloc technology (AQBFT) yielded comparatively lower growth performance in both fish and plants relative to the floating-raft aquaponic recirculating system (AQ).